Pengabdian Kepada Masyarakat; Pemberdayaan Masyarakat Sadar Gizi Melalui Program GEBUK (Gerakan Atasi Gizi Buruk) - Zinnurain, Zinnurain; Mujiburrahman, Mujiburrahman (Jurnal Dedikasi Madani, 2025)
The purpose of this community service activity is to implement Community Service; Empowering Nutrition-Conscious Communities through the "GEBUK; Movement to Overcome Malnutrition" program in Bentek Village, Gangga District, North Lombok Regency for the 2024/2025 academic year. This activity is carried out collaboratively (in groups) with a small team. The methods and procedures for carrying out the activities include: 1) Conducting interviews with partners and the surrounding community. 2) Coordinating with the Village Government. 3) Conducting observations. 4) Conducting socialization/education for the community. 5) Documenting the process of the program being implemented. The target of this activity is the residents of Bentek village, with 14 pregnant women and 28 mothers with toddlers, in collaboration with the Posyandu cadres of Bentek village. The activity is conducted from October to December 2024. This activity was carried out by the service team, consisting of DPL and 10 KKN-T students from Mandalika University of Education. The result of this activity is that all participants understand the "GEBUK; Movement to Overcome Malnutrition" program, as well as the prevention, handling, and follow-up actions in addressing issues of malnutrition, stunting, and wasting if they occur in Bentek village. With strong synergy and shared commitment, this program has the potential to provide a uniformly positive impact on the entire community, creating a healthier and higher-quality future generation.